ChemInform Abstract: Regioselective Alkyl Transfer from Phosphonium Ylides to Functionalized Polyfluoroarenes. Issue 41 (7th October 2014) - Lu, Wei; Gao, Juan; Yang, Jing‐Kui; Liu, Lei; Zhao, Yuliang; Wu, Hai‐Chen
Abstract The regioselective alkyl transfer reaction is further applied in the synthesis of the pesticide tefluthrin (XII).